Dependence of vortex phase transitions in mesoscopic Bi2Sr2CaCuO8 superconductor at tilted magnetic fields - Dolz, M.I.; Pastoriza, H. (IOP Publishing, 2009)
Fil: Dolz, M.I. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina